Design and development of novel low speed wind turbine generator system - Alotaibi, Alowaid A R O (2022)
Nowadays, renewable energies are highly demanded as they are sustainable and environmentally friendly. One of the renewable energy is wind, and it can be harvested by using a wind turbine. There are two types of wind turbines: Horizontal Axis Wind Turbine (HAWT) and Vertical Axis Wind Turbine (VAWT). However the power generated in any system by natural phenomenon has lots of limitations because of the inconsistency in the supply of the energy by the source. Wind energy from nature environment has limitation and inconsistency. Sometimes there are wind energy and sometimes no wind energy. It is mandatory to design a system which produces continuous and repeated power for the effective use. Also, in some parts of the country the weather is unpredictable to apply wind turbine system because of the environment. Hence, the research aimed to design and development of novel low speed wind turbine generator system. The study focused on the design of a new concept to improve the energy harvested by wind turbines to be appropriate for the unpredictable wind energy condition in Malaysia. The concept involves the implementation of wind turbines and output booster circuit for wind turbine generator system, to increase the electricity generated. Although the system used electricity to start, the implementation of the wind turbine system with booster circuit should contribute to improve the electricity harvested so that the harvested electricity can cover the used electricity in the system. Before the configuration of wind turbine and booster circuit were manufactured, the concept of wind turbine was studied to get the best performance of energy harvesting system while booster circuit was simulated with the use of a program to obtain the power booster in the system. Savonius type of Vertical Axis Wind Turbine was used in this research. Then the wind turbine system and booster circuit were fabricated and tested. Results showed that double wind turbine system can generated 0.5 V of voltage and 0.41 W of power at 1 m/s of wind speed while the booster circuit improved the result of voltage and power. Then the integrated wind turbine system with booster circuit was verified for perpetual motion energy harvesting system by analysed the output of the turbine generator and the output from booster circuit. The voltage that can be generated by turbine generator was 6.7 V by using double wind turbine system and the voltage was increased to 13.4 V by booster circuit.